OPTIMIZATION OF BUILDING INTEGRATED PHOTOVOLTAIC APPLICATION IN VERTICAL HOUSING WITH PARAMETRIC METHOD - Triadi, Fajar
The use of fossil fuels as a source of electrical energy in residential areas accounts for a third of the total global carbon emissions. Excess carbon emissions have an impact on increasing the earth's temperature so that the issue of global warming and the energy crisis is inevitable. Globally, efforts to reduce the increase in the earth's temperature are carried out by converting fossil fuel energy sources into Renewable Energy (EBT). Indonesia as a tropical country has high solar potential which can be used as a source of clean energy in building performance. Building Integrated Photovoltaic (BIPV) is a more effective system than the Building Attached Photovoltaic (BAPV) system in maximizing the utilization of solar energy into ready-to-use electrical energy. However, the effectiveness of BIPV in Indonesia is constrained due to detailed installations and maintenance techniques that affect losses such as electrical mismatches and have an impact on cooling load energy. Digital developments in architecture are able to calculate complex designs by entering certain parameters, namely the parametric architectural approach. This study aims to perform parametric techno-economic calculations on the use of BIPV in the study object of energy-efficient flats prototypes in Indonesia. Data were collected by observing, measuring and reviewing literature on lighting variables in buildings and passive designs in energy-efficient flats. Data were analyzed in two stages using simulation software Rhinoceros and Ladybug. In the first stage, the data is converted into digital modeling to calculate the solar passive gain on passive design elements of flats. The results of the first stage are scenarios of the most optimal PV laying pattern obtained from parametric analysis. Each scenario is continued in the second stage of analysis, which is an evaluation of the cooling load on the apartment housing units. The results obtained are in the form of energy comparisons between model scenarios.